2022
DOI: 10.1039/d2tc02287g
|View full text |Cite
|
Sign up to set email alerts
|

Chromaticity coordinate vector principle for charge-transfer-type thermochromic material design: case of Fe/Cr-(co)doped α-Al2O3host

Abstract: Charge-transfer-type thermochromic materials gain increasing research interest due to its smart character of reversibly continuous color-change presenting with temperature. However, the interaction between different chromophore in the same host matrix...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Perovskite-structure oxides are a class of oxygen-defect-sensitive materials with many defect-related applications. ,, Among these, perovskite-structure stannates (ASnO 3±δ ) are one of the most important families of oxygen-defective materials with applications in oxygen ions and H + conductors. , The oxygen vacancy formation energy is low, which results in defects that can be tuned by ultraviolet light irradiation and low oxidation states cation substitution of Sn 4+ . , In previous work, we have found the thermochromism of different chromophore groups in charge-transfer-type inorganic host follow a chromaticity vector principle . It is well-known that the electronic and optical behaviors of Sn-based oxide materials are sensitive to oxygen defects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perovskite-structure oxides are a class of oxygen-defect-sensitive materials with many defect-related applications. ,, Among these, perovskite-structure stannates (ASnO 3±δ ) are one of the most important families of oxygen-defective materials with applications in oxygen ions and H + conductors. , The oxygen vacancy formation energy is low, which results in defects that can be tuned by ultraviolet light irradiation and low oxidation states cation substitution of Sn 4+ . , In previous work, we have found the thermochromism of different chromophore groups in charge-transfer-type inorganic host follow a chromaticity vector principle . It is well-known that the electronic and optical behaviors of Sn-based oxide materials are sensitive to oxygen defects.…”
Section: Introductionmentioning
confidence: 99%
“…37,38 In previous work, we have found the thermochromism of different chromophore groups in charge-transfer-type inorganic host follow a chromaticity vector principle. 39 It is well-known that the electronic and optical behaviors of Snbased oxide materials are sensitive to oxygen defects. For example, the thermochromic property of β-Bi 2 Sn 2 O 7 shows calcination duration-dependent color evolution behavior.…”
Section: Introductionmentioning
confidence: 99%
“…However, all of the materials mentioned above have their limitations, vanadium oxide and molybdenum oxides mainly change color below 300 • C 21,22 ; rare-earth garnet structural oxide has good thermal stability but their visible spectra do not differ significantly at different temperatures, which indicates that the thermochromism is not significant 18,23 ; transition metal-doped oxide exhibit thermochromism at higher temperature (such as Y-doped Bi 2 O 3 20 at 20-777 • C, Co-doped ZnO 24 at 25-800 • C, and Co-doped TiO 2 25 at 20-800 • C), but their color-temperature correspondence has not been clearly explored. Recently, Yuan et al 26 have reported that the CIE-L × ab parameter can be described as a function of temperature for Fe/Cr-(co)doped α-Al 2 O 3 , but the function is close to a horizontal line and has a large error, which limits its further application. For this reason, it is urgently necessary to further investigate the high-temperature thermochromic mechanism and explore the color-temperature correspondence in the field of high-temperature thermochromic material for thermal indication.…”
Section: Introductionmentioning
confidence: 99%
“…Near-infrared light (700–1400 nm) is an electromagnetic wave that exists between visible and mid-infrared light and is greatly utilized in plant growth, night vision, medical imaging, food analysis, and so on. In recent years, NIR pc-LED, which is recognized as a new generation of NIR light source, has garnered a lot of attention due to its high efficiency and compact size. Cr 3+ is one of the most frequent activators of NIR phosphors. Its luminescence is greatly impacted by the crystal field with a narrow emission in a strong crystal field and a broadband one in a weak crystal field.…”
Section: Introductionmentioning
confidence: 99%